Cerebrovascular remodeling in aging and neurodegenerative disease progression - Halvorsen, Samuel C.; Gkousioudi, Anastasia; Nicks, Raymond; Alvarez, Victor E.; Bigio, Irving J.; Zaia, Joseph; Stein, Thor D.; Zhang, Yanhang (Frontiers in Bioengineering and Biotechnology, 2025)
The cerebrovasculature is responsible for supplying oxygenated blood and nutrients to the brain and removing neurotoxic buildup. With age, trauma, and disease, the structural constituents of cerebral arteries including the extracellular matrix and smooth muscle cells are subject to remodeling and degradation. Cerebrovascular dysfunction can have detrimental impacts on the brain and is closely associated with cognitive impairment. Clinical studies have found that cerebrovascular dysfunction is correlated with cognitive decline in neurodegenerative diseases including Alzheimer’s disease (AD) and chronic traumatic encephalopathy (CTE). However, cerebrovascular changes during the progression of neurological disorders remain to be understood. Using matched and parallel studies of cerebrovasculature and brain tissue, this study set out to determine the temporal development of cerebrovascular remodeling and neurodegenerative disease progression. We examined changes to human anterior cerebral arteries (ACAs) from subjects with various degrees of AD and CTE neuropathology. Using biaxial inflation-extension testing, histological staining, and multiphoton imaging, we examined changes to the mechanical response and to the ACA wall structure. We found circumferential stiffening of the ACA with age. Furthermore, a minor relationship was reported between ACA stiffening and elevated levels of tau-based neuropathologies including neurofibrillary tangles, characteristic of both AD and CTE. Histological and multiphoton structural studies of the ACAs revealed smooth muscle cell atrophy at the media-adventitia interface and disorganization and straightening of adventitial collagen with age and disease. Our study reveals changes to the extracellular and cellular components of cerebral arteries that help describe the functional alterations of cerebrovasculature. Results from this study shed light on the complex relationship between cerebrovascular remodeling and neurodegenerative disease progression.